Product Development within Artificial Intelligence, Ethics and Legal Risk Exemplary for Safe Autonomous Vehicles - Winkle, Thomas; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2022)
This open-access-book synthesizes a supportive developer checklist considering sustainable Team and agile Project Management in the challenge of Artificial Intelligence and limits of image recognition. The study bases on technical, ethical, and legal requirements with examples concerning autonomous vehicles. As the first of its kind, it analyzes all reported car accidents state wide (1.28 million) over a 10-year period. Integrating of highly sensitive international court rulings and growing consumer expectations make this book a helpful guide for product and team development from initial concept until market launch. The author Thomas Winkle (Prof. Dr.-Ing., MBA Communication & Leadership) is a multiple author in best-selling Springer books such as (3z(BAutonomous Driving: Technical, Legal and Social Aspects(3y (Bor the (3z(BHandbook of Driver Assistance Systems(3y(B. His work bases on three decades in sustainable team consulting as employee and researcher in the legal departments of three car manufacturers as well as a professor at IU International University and TU Munich. Thomas Winkle received the Volkswagen research award for his significant Human-Centered Design into the development of the Automatic Emergency Brake. He was responsible to prepare the ADAS Code of Practice. As consultant at international courts, he links Artificial Intelligence, Ethics, Sustainable Agile Management, Mindful Communication and Law using Autonomous Vehicles example definition requirements.s
Introduction -- Findings From Traffic Accident Analysis -- Analysis Of Poor Visibility Real-World Test Scenarios -- Technical, Legal, And Economic Risks -- Qualitative Interviews With Developers -- Consulting Concept To Develop New Systems -- Summary And Discussion -- Summary And Discussion.
Keywords: Automotive engineering; Building laws; Computational intelligence; Production engineering; Automotive Engineering; Building Law for Engineers and Architects; Computational Intelligence; Mechanical Process Engineering